Design and performance analysis of airbag-soft-manipulator according to characteristic parameters - Liu, Peng (Strojniški vestnik, 2020)
Manipulators are increasingly used in mechanical manufacturing due to the needs of industrial automation. The shortcomings of traditional manipulators, such as those in relation to their flexibility, interactivity, and safety, lead to certain limitations in their application for variable shapes and fragile objects. Given the above shortcomings of traditional manipulators, this research analysed a friction-enhanced multi-airbag soft manipulator and its performance. Analysis results of characteristic parameters show that the structure of the airbag soft manipulator is optimized, and the structural design and manufacture of the soft manipulator are completed. Deformation of the manipulator base material is described by the Neo-Hooke strain energy function, and the strain energy function coefficient is derived by obtaining the characteristic parameters of the material through tensile experiments. Finite element analysis of the manipulator is performed according to the determined strain energy function. The influence of the characteristic parameters on the mechanical bending of the manipulator is studied. Theoretical analysis proves the validity of the finite element analysis. The structural parameters of the manipulator are finally determined according to the simulation analysis results. The control system is designed according to the driving method and working mode of the soft manipulator to perform the soft manipulator grasp experiment. The manipulator can lift a weight of 300 g, thereby indicating that the soft manipulator designed in this paper has a good application effect and prospects.
Keywords: characteristic parameters; eksperimenti s prijemanjem; funkcija deformacijskega dela; grasp experiments; manipulatorji; metoda končnih elementov; optimizacija; optimized; soft manipulators; značilni parametri